Rainbow™ Universal CPG: A Versatile Solid Support for Oligonucleotide Synthesis. (April 1997) - Nelson, P.S.; Muthini, S.; Vierra, M.; Acosta, L.; Smith, T.H.
We have developed a universal solid support, termed Rainbow™ Universal CPG, for use in automated oligonucleotide synthesis. The universal solid support allows any oligodeoxyribonucleotide sequence to be synthesized from a single type of controlled pore glass (CPG) support. Deprotection of oligodeoxyribonucleotides was optimized using 0.5 M LiCl in concentrated ammonium hydroxide. PCR experiments using three different sets of primers proved that the 3′-hydroxyl function of oligodeoxyribonucleotides synthesized from Rainbow Universal CPG was retained. This universal solid support shows promise for replacing the standard nucleoside CPG supports.